Multiple influence of immune cells in the bone metastatic cancer microenvironment on tumors - Chen, Shixin; Lei, Jiangchu; Mou, Haochen; Zhang, Wenkan; Jin, Lingxiao; Lu, Senxu; Yinwang, Eloy; Xue, Yucheng; Shao, Zhenxuan; Chen, Tao; Wang, Fangqian; Zhao, Shenzhi; et al. (Frontiers in Immunology, 2024)
Bone is a common organ for solid tumor metastasis. Malignant bone tumor becomes insensitive to systemic therapy after colonization, followed by poor prognosis and high relapse rate. Immune and bone cells in situ constitute a unique immune microenvironment, which plays a crucial role in the context of bone metastasis. This review firstly focuses on lymphatic cells in bone metastatic cancer, including their function in tumor dissemination, invasion, growth and possible cytotoxicity-induced eradication. Subsequently, we examine myeloid cells, namely macrophages, myeloid-derived suppressor cells, dendritic cells, and megakaryocytes, evaluating their interaction with cytotoxic T lymphocytes and contribution to bone metastasis. As important components of skeletal tissue, osteoclasts and osteoblasts derived from bone marrow stromal cells, engaging in 'vicious cycle' accelerate osteolytic bone metastasis. We also explain the concept tumor dormancy and investigate underlying role of immune microenvironment on it. Additionally, a thorough review of emerging treatments for bone metastatic malignancy in clinical research, especially immunotherapy, is presented, indicating current challenges and opportunities in research and development of bone metastasis therapies.